Genetic variation in growth and stem form characteristics in acacia auriculiformis - Venkateswarlu, Perugupalli; Awang, Kamis; Abd Shukor, Nor Aini (Malaysian Society of Applied Biology, 1994)
Significant differences (p < O.Ol) were found among 28 provenances of Acacia auriculiformis for height. diameter breast height (OBH). basal diameter and stem form. The average height of the provenances ranged from 6.6 to 10.4 m and OBH ranged from 5.6 to 9.6 cm. Low genetic parameters were recorded for all the characters indicating that only limited genetic improvement can be obtained by selecting any of the provenances for use at the location tested. OBH had the highest heritability estimation (0.46) and relatively high potential for genetic advance (expressed as a percentage of the mean. 18%) among the characters examined. Thus. OBH can be considered as a possible character to be used in selecting the A. auriculiformis provenances tested for advanced-generation improvement.